Sulfydryl-containing alkyl polysiloxane polymer as well as preparation method and application thereof

By using alkyl polysiloxane polymer containing sulfhydryl groups as a protective agent on the FPC plate, the problem of easy corrosion on the copper surface of the FPC plate in the prior art is solved, and a dense protective film is formed, which significantly improves the protective effect and service life.

CN119529288APending Publication Date: 2025-02-28POLYONTECH ADVANCED MATERIAL SHANGHAI CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411851449.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent corrosion of copper surfaces on flexible circuit boards (FPC boards) for a long time, especially in environments with high humidity. Commonly used corrosion-inhibiting protective agents are prone to wear and poor water solubility, and cannot form a dense protective film.

Method used

An sulfhydryl-containing alkyl polysiloxane polymer is used as a protective agent. This polymer can form a strong complexing effect with the copper surface and forms a dense protective film by crosslinking during drying, which has excellent water resistance and salt spray resistance.

Benefits of technology

It realizes the formation of a dense protective film on the copper surface of the FPC plate for a long time, significantly improves the protection effect, extends the service life of the FPC plate, and simplifies the process and avoids pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190690420000071
    Figure BDA0005190690420000071
  • Figure BDA0005190690420000081
    Figure BDA0005190690420000081
  • Figure BDA0005190690420000091
    Figure BDA0005190690420000091
Patent Text Reader

Abstract

The invention discloses a sulfydryl-containing alkyl polysiloxane polymer which is characterized by comprising the following components in parts by weight: 5-15 parts of 3-mercaptopropyl trialkoxysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 5-15 parts of alkyl polysiloxane, 20 to 40 parts of trialkoxy siloxane with C12 to 16 alkyl groups; 30 to 50 parts of alkyl trialkoxy siloxane with a carbon number of 1 to 3; and 0 to 5 parts of gamma-aminopropyl triethoxy silane. The invention also discloses a preparation method and application of the compound. A water-based metal surface protective agent formed by the sulfydryl-containing alkyl polysiloxane polymer prepared by the method under the action of an emulsifier can effectively protect copper metal on the surface of a flexible printed board, effectively improve the water resistance and salt spray resistance effects and provide long-term stability and protection effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface treatment of flexible circuit boards, and in particular relates to an alkyl polysiloxane polymer containing a mercapto group, and a preparation method and application thereof. Background Art

[0002] Flexible Printed Circuit (FPC), also known as flexible circuit board, has the characteristics of high wiring density, light weight and thin thickness, and is widely used in mobile phones, computers, digital cameras, medical equipment, aerospace, wearable smart devices and new energy electric vehicles. Because it can be bent, folded and wound freely, it can be moved and stretched in three-dimensional space; it has excellent heat dissipation, can further reduce the volume, achieve lightweight, miniaturization and thinness, and achieve the integration of original device and wire connection, playing a pivotal role in electronic products and components.

[0003] The preparation of flexible circuit boards includes many production processes, and there are various product designs and solutions according to different applications. According to the bonding method of copper foil and substrate, one is a flexible board with glue, which means that the copper foil and substrate are bonded together by colloid; the other is a flexible board without glue, which uses hot pressing to press the copper foil and substrate together. In comparison, its flexibility, bonding strength between copper foil and substrate, pad and flatness are better than those of flexible boards with glue. For example, COF boards with bare chips mounted on flexible boards.

[0004] Although FPC boards have many advantages, especially in the increasingly diversified electronic products, they are widely used, but they also have some defects, such as relatively poor temperature resistance, and are easily affected by high temperature environments, which limits their application in high temperature environments. In addition, they have a limited lifespan and are susceptible to oxidation, corrosion, etc., requiring regular replacement and maintenance. Through many technological innovations and research and development of substrate materials, the defects of temperature resistance can be basically overcome, and electronic products are rarely used at extreme temperatures. However, oxidation and corrosion caused by environmental factors always exist, especially the changes in temperature, humidity, ion corrosion, solvents, greases and other conditions in the application environment, which not only affect the service life of the FPC board, but also have a relatively large impact on the use of terminal products. Therefore, it has always been urgent and important to find a method that can effectively provide long-term protection for FPC boards.

[0005] The parts of FPC boards that are most susceptible to corrosion and performance impact are mainly metal parts. Since the metals used are mainly copper and silver, especially copper metal, which has excellent electrical conductivity and relatively high cost performance, it has been more widely used.

[0006] However, copper is also more susceptible to the influence of the external environment, especially moisture and ion corrosion. A large number of technicians have done a lot of work on how to alleviate copper corrosion and improve its protection, and there are also many literature reports.

[0007] Patent CN112853341A discloses a cleaning and anti-oxidation process for the surface treatment of copper foil of a printed circuit board, which can effectively prevent oxidation of the copper foil surface by using steps such as degreasing-one water washing-micro-etching-two water washing-pickling-three water washing-one drying-anti-oxidation treatment-two drying-four water washing-drying board. The document does not provide a specific description of the anti-oxidation treatment agent, but only mentions that the pH of the copper antioxidant is controlled at 3.2±0.4. According to the description in the document, highly corrosive substances such as sulfuric acid and formic acid need to be used in the treatment process, which is not suitable for the treatment of printed FPC boards.

[0008] Patent CN114196484A discloses a pore-forming agent used in the manufacture of printed circuit boards, including a high molecular weight cationic surfactant, an acid, a small molecule surfactant, a salt and water, which is used for cleaning the drilling holes of circuit boards. In this document, a cationic surfactant is used to provide a certain anti-corrosion effect on metals, and an acid and a salt are still used to achieve the cleaning of the drilling holes.

[0009] Patent CN110358423A discloses a cleaning and anti-oxidation process of a copper-silver protective agent and a copper alloy, which includes using benzotriazole, sodium gluconate and polyethylene glycol to form a protective layer on the copper surface to achieve an anti-oxidation effect. From the above disclosed literature, it can be seen that the use of cationic surfactants and benzotriazole, a commonly used copper surface protective agent, can indeed play a certain role in corrosion inhibition and protection of the copper surface.

[0010] However, for FPC boards, there are still problems during long-term use. In particular, this type of corrosion inhibitor cannot form a dense film-forming substance on the copper surface, which is easily worn away and loses its protective effect. In addition, this type of corrosion inhibitor has a certain water solubility, which can easily cause water penetration in a humid environment, causing copper corrosion and losing its protective effect. Summary of the invention

[0011] Based on the above-mentioned defects of the prior art, the present invention discloses an alkyl polysiloxane polymer containing a mercapto group, a preparation method and an application thereof.

[0012] The protective agent prepared from the mercapto-containing alkyl polysiloxane polymer of the present invention can overcome the defects of easy wear and water solubility in the prior art during long-term use, and can form a dense protective film on the copper surface. The protective film has excellent water resistance and salt spray resistance, can effectively protect the metal of the FPC board for a long time, and greatly improves the service life of the FPC board and the maintenance of its performance.

[0013] The present invention adopts an alkyl polysiloxane polymer containing a mercapto group as a protective agent. The mercapto group in the polymer can effectively complex with copper and has excellent adhesion. During the drying process, the siloxane groups in the polymer will be cross-linked to form a dense protective film with excellent water resistance and wear resistance, further improving the protective effect.

[0014] In order to achieve the purpose of the present invention, the technical solution adopted is:

[0015] An alkyl polysiloxane polymer containing a mercapto group comprises the following components, calculated by weight, the sum of the components being 100 percent:

[0016] 5-15 parts of 3-mercaptopropyltrialkoxysiloxane;

[0017] 20-40 portions of C 12-16 Alkyl trialkoxysiloxanes;

[0018] 30-50 portions of C 1-3 Alkyl trialkoxy siloxane;

[0019] 0-5 parts of gamma-aminopropyltriethoxysilane.

[0020] An alkyl polysiloxane polymer containing a mercapto group, calculated by weight, further comprising:

[0021] 0.5-1.5 parts of a catalyst, wherein the catalyst is a weakly basic ion exchange resin;

[0022] 0.5-5 parts of deionized water, wherein the conductivity of the deionized water is 0.05-1 us / cm.

[0023] In a preferred embodiment of the present invention, the 3-mercaptopropyl trialkoxysiloxane is any one or more of 3-mercaptopropyl trimethoxysiloxane, 3-mercaptopropyl triethoxysiloxane or 3-mercaptopropyl tripropoxysiloxane.

[0024] 7-12 parts of 3-mercaptopropyltriethoxysiloxane is preferred.

[0025] In a preferred embodiment of the present invention, the C 12-16The alkyl trialkoxysiloxane is any one or more of dodecyl trimethoxysiloxane, dodecyl triethoxysiloxane, tetradecyl trimethoxysiloxane, tetradecyl triethoxysiloxane, hexadecyl trimethoxysiloxane or hexadecyl triethoxysiloxane, preferably 25-38 parts.

[0026] In a preferred embodiment of the present invention, the C 1-3 The alkyl trialkoxysiloxane is any one or more of methyl trimethoxysiloxane, ethyl trimethoxysiloxane, ethyl trimethoxysiloxane or ethyl triethoxysiloxane. Preferably 35-45 parts.

[0027] In a preferred embodiment of the present invention, the mass fraction of the γ-aminopropyltriethoxysilane is 0-4 parts.

[0028] In a preferred embodiment of the present invention, the mass fraction of the catalyst is 0.6-1.2 parts.

[0029] In a preferred embodiment of the present invention, the deionized water is deionized water obtained by ion exchange or distillation, and the mass fraction of the deionized water is 1-5 parts.

[0030] A method for preparing an alkyl polysiloxane polymer containing a mercapto group comprises the following steps:

[0031] The 3-mercaptopropyl triethoxysiloxane, C 12-16 Alkyl triethoxysiloxane and C 1-3 Alkyl triethoxysiloxane and γ-aminopropyl triethoxysilane are added into a reaction bottle equipped with a distillation and dropping device;

[0032] Then, the catalyst is added and heated to 120-125° C., and deionized water is dripped into the reaction bottle, and ethanol is distilled out during the dripping process;

[0033] After the addition is completed, continue to react at 120-125°C for 2-3 hours, then raise the temperature to 140-150°C for 2-3 hours until there is no distillate and stop heating;

[0034] The temperature is lowered to no higher than 80° C., and the catalyst is removed by hot filtration to obtain the light yellow to yellow viscous alkyl polysiloxane polymer containing a mercapto group.

[0035] The invention discloses an application of an alkyl polysiloxane polymer containing a mercapto group, wherein the application is to prepare a protective agent for the metal surface of a flexible printed circuit board, specifically, the alkyl polysiloxane polymer containing a mercapto group is dissolved in an organic solvent, a nonionic emulsifier is added for emulsification reaction, a defoamer is added, and the mixture is heated to 55-60°C, and deionized water at a temperature of 45-50°C is slowly added at a rotation speed of 400-500 rpm, and the mixture is stirred for reaction, and then homogenized to obtain a stable emulsified protective agent liquid.

[0036] In a preferred embodiment of the present invention, the organic solvent is ethylene glycol butyl ether, the nonionic emulsifier is a nonionic emulsifier with HLB=10-18, and the defoamer is an organosilicon defoamer.

[0037] The beneficial effects of the present invention are:

[0038] First, the alkyl polysiloxane polymer containing mercapto groups prepared in the present invention can form a strong complexation on the surface of copper and maintain long-term adhesion.

[0039] Second, the mercaptoalkyl polysiloxane polymer in the metal surface protective agent prepared in the present invention undergoes cross-linking during the drying process to form a dense protective film, which has excellent waterproof and wear-resistant effects, can provide protection for a long time, and provides excellent water resistance and salt spray resistance.

[0040] Thirdly, the prepared metal protective agent containing mercaptoalkyl polysiloxane polymer does not require pretreatment of the surface of the FPC board and can be directly cut and sealed after use, thereby simplifying the process and avoiding pollution.

[0041] Fourthly, the prepared metal protective agent containing the mercaptoalkyl polysiloxane polymer uses water as a carrier and has excellent environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 1 (Blank control, copper surface rust was obvious after 12h).

[0043] Figure 2 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 2 (P1, 96h).

[0044] Figure 3 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 3 (P3, 96h).

[0045] Figure 4 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 4 (P4, 96h).

[0046] Figure 5 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 5 (P6, 96h).

[0047] Figure 6 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 6 (Comparative Example 1, the copper surface was severely corroded after 48 hours).

[0048] Figure 7 The salt spray resistance test diagram of the metal surface protective agent of the FPC board of the present invention Figure 7 (Comparative Example 2, the copper surface was obviously corroded after 24 hours). DETAILED DESCRIPTION

[0049] If not otherwise specified, as described in the present invention, each preferred solution is combined with other preferred solutions to form a new technical solution. Due to limited space, the combined technology is not described in detail, however, all technical solutions combined with each other should be considered to have been clearly described in the present invention.

[0050] The following examples are used to illustrate the process and composition of the present invention. These examples are helpful for those skilled in the art to understand the present invention. However, the present invention is not limited to these examples.

[0051] The catalyst used in the examples is a weakly basic ion exchange resin.

[0052] The deionized water used in the examples has a conductivity of 0.05-1 us / cm.

[0053] Preparation method of mercaptoalkyl polysiloxane polymer S:

[0054] Containing 5-15wt% of 3-mercaptopropyl triethoxysiloxane, 20-40wt% of C 12-16 Alkyl triethoxysiloxane, 30-50%wt C 1-3 alkyl triethoxysiloxane, 0-5wt% of γ-aminopropyl triethoxysilane are added to a reaction bottle with a distillation and dropping device, and then 0.5-1.5wt% of weak alkaline ion exchange resin catalyst is added, heated to 120-125°C, and 0.5-5wt% of deionized water is added to the reaction bottle at the same time, and the dropping time is 4 hours. Ethanol is distilled during the dropping process. After the dropping is completed, continue to react at 120-125°C for 2 hours, then heat to 140-150°C for 3 hours, stop heating until there is no distillate, cool to 80°C, and remove the ion exchange resin by hot filtration to obtain a light yellow to yellow viscous mercaptoalkyl polysiloxane polymer S.

[0055] Example 1: Mercaptoalkylpolysiloxane polymer S1:

[0056] According to the above-mentioned preparation method of siloxane polymer, 10wt% of 3-mercaptopropyltriethoxysiloxane, 45wt% of hexadecyltriethoxysiloxane, 40wt% of methyltriethoxysiloxane, 1.5wt% of γ-aminopropyltriethoxysilane, 0.6wt% of catalyst, 2.9wt% of deionized water was added dropwise for reaction to obtain a viscous light yellow polysiloxane polymer S1.

[0057] Example 2: Mercaptoalkylpolysiloxane polymer S2:

[0058] According to the above-mentioned preparation method of siloxane polymer, 15wt% of 3-mercaptopropyltriethoxysiloxane, 20wt% of dodecyltriethoxysiloxane, 38wt% of ethyltriethoxysiloxane, 2.5wt% of γ-aminopropyltriethoxysilane, 0.5wt% of catalyst, 4% deionized water was added dropwise for reaction to obtain a viscous light yellow polysiloxane polymer S2.

[0059] Example 3: Mercaptoalkylpolysiloxane polymer S3:

[0060] According to the above-mentioned preparation method of siloxane polymer, 5wt% of 3-mercaptopropyltriethoxysiloxane, 50wt% of dodecyltriethoxysiloxane, 36.2% of methyltriethoxysiloxane, 5% of γ-aminopropyltriethoxysilane, 1.0wt% of catalyst, and 2.8% of deionized water are added to react to obtain a viscous light yellow polysiloxane polymer S3.

[0061] Example 4: Mercaptoalkylpolysiloxane polymer S4:

[0062] According to the above-mentioned preparation method of siloxane polymer, 12wt% of 3-mercaptopropyltriethoxysiloxane, 37wt% of hexadecyltriethoxysiloxane, 43.4wt% of methyltriethoxysiloxane, 4.2wt% of γ-aminopropyltriethoxysilane, 0.8wt% of catalyst, 2.6% of deionized water were added dropwise to react to obtain a viscous light yellow polysiloxane polymer S4.

[0063] Example 5: Mercaptoalkylpolysiloxane polymer S5:

[0064] According to the above-mentioned preparation method of siloxane polymer, 14.5wt% of 3-mercaptopropyltriethoxysiloxane, 34.1wt% of hexadecyltriethoxysiloxane, 50% of methyltriethoxysiloxane, 0.8wt% of catalyst, and 0.6% of deionized water were added dropwise to react to obtain viscous light yellow polysiloxane polymer S5.

[0065] Example 6-11: Preparation method of FPC board metal surface protective agent P:

[0066] A certain amount of the above prepared mercaptoalkyl polysiloxane polymer (S1-S5) was dissolved in a small amount of ethylene glycol butyl ether, and then a certain amount of nonionic emulsifier (E1310 with HLB = 10-18) was added.

[0067] emulsifier and / or Tween 80), and then add 0.05% of silicone defoamer. Then heat to 55-60°C, slowly add deionized water at a temperature of 45-50°C at a speed of 400-500, and add for 1 hour. After the addition is completed, stir for 1.5 hours, and then use a high-speed homogenizer at a speed of 4500 for 20-25 minutes until a stable emulsified liquid is formed, which is the metal surface protective agent P1-P6 (Table 1).

[0068] Table 1: Examples 6-11 Metal Surface Protectants P1-P6

[0069]

[0070]

[0071] The organosilicon defoamer in the present invention only has a defoaming effect, and other defoamers can also be used.

[0072] Comparative Example 1:

[0073] 10 wt % of 3-mercaptopropyl triethoxysiloxane, 45 wt % of hexadecyl triethoxysiloxane, 40 wt % of methyl triethoxysiloxane and 1.5 wt % of γ-aminopropyl triethoxysilane were mixed uniformly and then used.

[0074] Comparative Example 2:

[0075] 15wt% of dodecyl mercaptan, 20wt% of ethylene glycol butyl ether, 5wt% of Tween 80 and 3wt% of E1310 emulsifier were added to the reaction bottle, and then heated to 60-65°C. 57wt% of 60°C deionized water was slowly added under stirring at 400-500 rpm, and then stirred for 1 hour. The mixture was switched to a homogenizer and homogenized at 4500 rpm for 20 minutes to form an emulsion.

[0076] FPC board metal surface protective agent test method:

[0077] Water resistance test:

[0078] The prepared Examples 6, 8, 9, 11 and Comparative Examples 1 and 2 were diluted with deionized water to 10% solid content, and then the untreated FPC board was immersed in the diluted protective agent solution for 2 minutes. After taking it out, it was air-dried for 2 minutes, and then baked in a drying oven at 120°C for 15 minutes. Take it out and cool it to room temperature. Then put the treated board into tap water. Observe the surface rust state for 7 days, 15 days, 30 days, and 60 days. The test results are shown in Table 2.

[0079] Table 2: Water resistance test results of FPC board metal surface protective agent

[0080]

[0081] Salt spray resistance test:

[0082] The prepared Examples 6, 8, 9, 11 and Comparative Examples 1 and 2 were diluted with deionized water to 10% solid content, and then the untreated FPC board was immersed in the diluted protective agent solution for 2 minutes, taken out, dried for 2 minutes, and then baked in a drying oven at 120°C for 15 minutes. Take it out and cool it to room temperature. Then put the treated board into a neutral salt spray box for salt spray resistance test (5% sodium chloride, temperature 35 degrees), and observe the salt spray resistance status of 12 hours, 24 hours, 48 ​​hours, and 96 hours.

[0083] The test results and pictures are shown in Table 3 and Figure 1-7 :

[0084] Table 3: FPC board metal surface protective agent salt spray resistance test results

[0085]

[0086] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. An alkyl polysiloxane polymer containing a mercapto group, characterized in that Calculated by weight, it includes the following components, the sum of each component is 100%: 5-15 parts of 3-mercaptopropyltrialkoxysiloxane; 20-40 portions of C 12-16 Alkyl trialkoxysiloxanes; 30-50 portions of C 1-3 Alkyl trialkoxy siloxane; 0-5 parts of gamma-aminopropyltriethoxysilane.

2. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 1, characterized in that: Calculated by weight, it also includes: 0.5-1.5 parts of a catalyst, wherein the catalyst is a weakly basic ion exchange resin; 0.5-5 parts of deionized water, wherein the conductivity of the deionized water is 0.05-1 us / cm.

3. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 1, characterized in that: The 3-mercaptopropyl trialkoxysiloxane is any one or more of 3-mercaptopropyl trimethoxysiloxane, 3-mercaptopropyl triethoxysiloxane or 3-mercaptopropyl tripropoxysiloxane.

4. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 1, characterized in that: The C 12-16 The alkyl trialkoxysiloxane is any one or more of dodecyltrimethoxysiloxane, dodecyltriethoxysiloxane, tetradecyltrimethoxysiloxane, tetradecyltriethoxysiloxane, hexadecyltrimethoxysiloxane or hexadecyltriethoxysiloxane.

5. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 1, characterized in that: The C 1-3 The alkyltrialkoxysiloxane is any one or more of methyltrimethoxysiloxane, ethyltrimethoxysiloxane, ethyltrimethoxysiloxane or ethyltriethoxysiloxane.

6. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 1, characterized in that: The mass fraction of the γ-aminopropyltriethoxysilane is 0-4 parts.

7. An alkyl polysiloxane polymer containing a mercapto group as claimed in claim 2, characterized in that: The mass fraction of the catalyst is 0.6-1.2 parts; The deionized water is deionized water obtained by ion exchange or distillation, and the mass fraction of the deionized water is 1-5 parts.

8. A method for preparing a mercapto-containing alkyl polysiloxane polymer as described in any one of claims 1 to 7, characterized in that: The steps include: The 3-mercaptopropyl triethoxysiloxane, C 12-16 Alkyl triethoxysiloxane and C 1-3 Alkyl triethoxysiloxane and γ-aminopropyl triethoxysilane are added into a reaction bottle equipped with a distillation and dropping device; Then, the catalyst is added and heated to 120-125° C., and deionized water is dripped into the reaction bottle, and ethanol is distilled out during the dripping process; After the addition is completed, continue to react at 120-125°C for 2-3 hours, then raise the temperature to 140-150°C for 2-3 hours until there is no distillate and stop heating; The temperature is lowered to no higher than 80° C., and the catalyst is removed by hot filtration to obtain the light yellow to yellow viscous alkyl polysiloxane polymer containing a mercapto group.

9. An application of an alkyl polysiloxane polymer containing a mercapto group as described in any one of claims 1 to 7, characterized in that: The application is to prepare a protective agent for the metal surface of a flexible printed circuit board, specifically, the alkyl polysiloxane polymer containing a mercapto group is dissolved in an organic solvent, a nonionic emulsifier is added for emulsification reaction, a defoamer is added, and the mixture is heated to 55-60°C, and deionized water at a temperature of 45-50°C is slowly added at a rotation speed of 400-500, stirred for reaction, and then homogenized to obtain a stable emulsified protective agent liquid.

Citation Information

Patent Citations

  • Cleaning antioxidation process of copper-silver protection agent and copper alloy

    CN110358423A